Pengaruh Latihan Relaksasi Otot Progresif bagi Lansia dengan Kualitas Tidur Buruk - Nungki Marlian Yuliadarwati; Kurnia Putri Utami (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The impact of changes in the physiological system at age is a disturbance and a decrease in sleep quality. A reduction in sleep quality can affect the life expectancy of the elderly. In Indonesia, almost half of the total elderly (50%) have problems with sleep quality and experience serious sleep problems reaching 17%. The island of Java, especially the East Java region, reported about 45% of the elderly experience sleep quality problems. The quality of sleep that does not get proper treatment can affect physical and psychological performance so that the rate of older adults decreases. One of the exercises that can be given is progressive muscle relaxation. Increasing the degree of health in the elderly can be done by progressive muscle relaxation, which aims to increase muscle relaxation so that the elderly are calmer to prepare for physical conditions and body physiology at night when going to sleep. The purpose of community service is to provide education on progressive muscle relaxation exercises to prevent and reduce poor sleep quality in the elderly at the Elderly Posyandu. The methods used were free examinations, counseling, leaflet distribution, and poster installation. The development of community service programs is more optimal with the integration of Posyandu program activities carried out regularly and continuously.